Kurangnya Ketertarikan Siswa Terhadap Mata Pelajaran IPS Di Tingkat SMP - Zahrotun Nahla; Bagus Setiawan; Tika Ulandari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the causes of junior high school students' lack of interest in social studies subjects. Students' lack of interest in social studies subjects is an obstacle to the success of social studies learning. This is because students who are not interested in social studies subjects will tend to underestimate social studies subjects. This research uses the library research method. This research went through steps which included searching for journals that were relevant to the title of our research, then identifying and classifying several sources, then we reviewed them descriptively and compiled the results of the systematic literature review into a journal. The results of this research show that the factors causing students' lack of interest in social studies subjects include the lack of relevance of learning material to everyday life, monotonous teaching methods, and students' perceptions of the difficulty of social studies subject matter. Apart from that, environmental factors and family support also play a role in influencing students' interest in learning social studies. Efforts to increase students' interest in social studies subjects involve improving the curriculum, developing innovative teaching methods, and increasing interaction between learning material and the context of students' daily lives. Apart from that, involving parents in supporting social studies learning can be an effective strategy in stimulating students' interest in learning social studies.